ANALISIS KINERJA MESIN PENDINGIN KOMPRESI UAP MENGGUNAKAN FE-36 SEBAGAI ALTERNATIF PENGGANTI R-22 - R Bagus Suryasa Majanasastrs (Jurnal Ilmiah Teknik Mesin, 2015)
This paper introduces developmental fluid FE-36 as potential replacement for R-22. FE-36 is fire extinguishingagent. It is a new fire extinguishing agent that is replacing Halon 1211 in portable extinguishers and othersteaming applications. FE-36 is non-corrosive, electrically nonconductive, free of residue, and has zero ozonedepletionpotential (ODP). At the last assessment from Environmental Protection Agency (EPA), indicatea very low level of toxicity. Key thermo-physical properties of both fluid material ware determined and itsthermodynamic performance in a modeling COP testing machine was evaluated thought computationalmodeling by using Genetron Properties 1.1. Based on data experiment, the COP of FE-36 has analysis andcompare to the COP of R-22. Comparison data COP show that average of COP of FE-36 to R-22 is more than80%.